Study of Lipid Profile during Late Reproductive Phase, Perimenopause and Postmenopause in North Indian Women - Ayaz Khurram Mallick; Marya Ahsan; Biswajit Das; Shikha Saxena; Sumeru Samanta; Simarpreet Kukreja (International Journal of Medical Research and Review, 2015)
Background: Perimenopause or menopausal transition is the phase which preceeds menopause and is characterized with fluctuation in estrogen levels. Several studies have been done to investigate the changes in lipid profile in premenopausal and postmenopausal women. Studies regarding the changes in lipid profile during perimenopause is scanty. This study was done to study the lipid profile in reproductive or premenopausal, perimenopausal and postmenopausal women.Materials and method: A case control study was done on 60 late reproductive phase, 60 perimenopausal and 60 postmenopausal women. Total cholesterol (TC), serum triglyceride and High Density Lipoprotein – Cholesterol (HDL-C) were determined with a fasting venous blood sample. Low Density Lipoprotein – Cholesterol (LDL-C) was calculated by Friedwald’s formula. TC/HDL cholesterol ratio and LDL/HDL cholesterol ratio were calculated and compared. Data was analyzed using Statistical Package for Social Sciences (SPSS) 17.0 version (SPSS Inc., Chicago, IL, USA).Results: Statistically significant increase in the total cholesterol, serum triglyceride and HDL-C levels and LDL/HDL cholesterol ratio in the perimenopausal was observed when compared with women in late reproductive age group. LDL- C and the TC/HDL-C ratio although increased was statistically not significant. Postmenopausal women showed statistically significant increase in TC, serum TG, LDL-C, TC/HDL-C ratio and LDL/HDL-C ratio.Conclusion: Adverse changes seen in the lipid profile during postmenopause begins during the perimenopause. As the perimenopause phase is a period of varied length, it is the optimal time for lifestyle style modification and preventive intervention in order to prevent cardiovascular risk in future.